Optimización de peso estructural para un chasis monoplaza Formula Student EB17 de la carrera Ingeniería Automotriz UPS sede Cuenca - Cuenca Ramón, Holger Santiago (2022)
This project was carried out with the purpose of optimizing the structural weight of a chassis, which was built with the FSAE 2016 regulations; from this it can be modified obtaining significant improvements. Thus knowing the most characteristic aspects for modeling and construction with the new 2022 rules.